2020
DOI: 10.1155/2020/1496756
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Traffic Flow of the Urban Signalized Intersection with a Straddling Work Zone

Abstract: Work zones widely exist on urban roads in many countries and have a significant negative impact on traffic. Few studies have focused on modeling the traffic flow of the work zone on the urban arterials, especially on the work zone at the intersections. In this paper, a microscopic model based on the social force theory for the traffic flow of the intersection with a specific work zone, called straddling work zone, is proposed. The model can capture the no lane division and irregular boundary characteristics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…At the same time, as the speed of the mobile construction zone increased, the average traffic risk decreased. The scholar proposed a microscopic model of traffic flow in a straddle work zone to capture the characteristics of no lane division and irregular boundaries that intersect with the straddle work zone, reflecting the effect of traffic flow from two opposite directions of the intersection road [11]. Finally, the entropy method was used for evaluation, and the results showed that the distance from the lower edge of the work zone to the centerline and the proportion of large vehicles occupying the work zone exerted the most significant influence on the signalized intersection.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, as the speed of the mobile construction zone increased, the average traffic risk decreased. The scholar proposed a microscopic model of traffic flow in a straddle work zone to capture the characteristics of no lane division and irregular boundaries that intersect with the straddle work zone, reflecting the effect of traffic flow from two opposite directions of the intersection road [11]. Finally, the entropy method was used for evaluation, and the results showed that the distance from the lower edge of the work zone to the centerline and the proportion of large vehicles occupying the work zone exerted the most significant influence on the signalized intersection.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, in an effort to alleviate the effects of construction work zones on traffic efficiency, researchers and policymakers in the field of transportation have been exploring various strategies. Some scholars have evaluated the impact of road construction through dynamic traffic allocation and compared alternative construction schedule plans in order to choose the optimal plan to reduce travel delays and improve road capacity [10,11]. Several studies have analyzed the impact of construction work zone length on road capacity [12][13][14].…”
Section: Introductionmentioning
confidence: 99%